Scale and skill in active management - Pástor, Ľuboš; Stambaugh, Robert F.; Taylor, Lucian A. (Journal of Financial Economics, 2015)
We empirically analyze the nature of returns to scale in active mutual fund management. We find strong evidence of decreasing returns at the industry level. As the size of the active mutual fund industry increases, a fund׳s ability to outperform passive benchmarks declines. At the fund level, all methods considered indicate decreasing returns, though estimates that avoid econometric biases are insignificant. We also find that the active management industry has become more skilled over time. This upward trend in skill coincides with industry growth, which precludes the skill improvement from boosting fund performance. Finally, we find that performance deteriorates over a typical fund׳s lifetime. This result can also be explained by industry-level decreasing returns to scale.